3
$\begingroup$

Find all positive integers m, n, p such that

$$(m+n)(mn+1)=2^p$$

Please give me some hints

Thanks

$\endgroup$
  • $\begingroup$ I proved m+1=t2^s, n-1=q2^s with t, q are odd numbers But ... . Just that $\endgroup$ – tangkhaihanh Nov 5 '13 at 10:32
  • $\begingroup$ what is $s$???? $\endgroup$ – user87543 Nov 5 '13 at 10:34
  • $\begingroup$ Is $p$ prime ? ${}{}{}{}$ $\endgroup$ – Amr Nov 5 '13 at 10:34
  • $\begingroup$ No, p is a positive number $\endgroup$ – tangkhaihanh Nov 5 '13 at 10:35
  • $\begingroup$ @tangkhaihanh: This is true for any integer... $\endgroup$ – MichalisN Nov 5 '13 at 10:37
1
$\begingroup$

We have $m+n=2^a$ and $mn+1=2^b$ with $a+b=p$. First note that both $m$ and $n$ need to be odd.

First case: Suppose $m=1$ or $n=1$, then the other is equal to $2^{p/2}-1$ and this is a solution for even $p$.

Now suppose $m>1$ so $b>a>1$. Adding the two equations above we get $(m+1)(n+1)=mn+1+m+n=2^a(2^{b-a}+1)$. Let $m+1=2^xw$ and $n+1=2^zy$ with $w,y$ odd, $x,z>0$ and $x+z=a$. Then $2^a=2^xw+2^zy-2$, so one of $x$ or $z$ needs to be $1$ (if both were $>1$ the RHS would be $\equiv 2\mod 4$.

Case $x=1$: We have $x+z=a$, so $z=a-1$. The equation for $2^a$ becomes $$ 2^a=2w+2^{a-1}y-2\geq 2^{a-1}y. $$ This implies $y=1$, since it is odd. We get $m-1=2w-2=2^{a-1}$ and $n+1=2^z=2^{a-1}$ and indeed this gives a solution.

Case $z=1$: The same just with $m$ and $n$ swapped.

So the only solutions are $m=1$ and $y=2^{p/2}-1$ and $(m,n)=(2^k\pm 1,2^k\mp 1)$

$\endgroup$
  • $\begingroup$ "so one of x or y needs to be 1" must "x or z" ? $\endgroup$ – tangkhaihanh Nov 5 '13 at 11:15
  • $\begingroup$ @tangkhaihanh: Yeah. Sorry for the notational difficulties here, I changed it while I was writing the answer. I hope my solution is correct but it's probably not the most elegant. $\endgroup$ – MichalisN Nov 5 '13 at 11:35
  • $\begingroup$ Please consider and describe in addition case $(m,n)=(2^k\pm 1, 2^k\mp 1)$. then $(m+n)(mn+1) = 2^{3k+1}$, $k\in \mathbb{N}$. Examples: $$(1+3)(1\cdot 3 +1) = 2^4;$$ $$(3+5)(3\cdot 5 +1) = 2^7;$$ $$(7+9)(7\cdot 9 +1) = 2^{10};$$ $$(15+17)(15\cdot 17 +1) = 2^{13};$$ $$...$$ $\endgroup$ – Oleg567 Nov 5 '13 at 12:40
  • $\begingroup$ @Oleg567, yes, i am wondering $\endgroup$ – tangkhaihanh Nov 5 '13 at 12:54
  • $\begingroup$ @Oleg567: Thank you! I forgot one crucial case! I'll add it. $\endgroup$ – MichalisN Nov 5 '13 at 14:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.